Synergies and tensions between universal health coverage and global health security: why we need a second ‘Maximizing Positive Synergies’ initiative - Ooms, Gorik; Beiersmann, Claudia; Flores, Walter; Hanefeld, Johanna; Müller, Olaf; Mulumba, Moses; Ottersen, Trygve; Sarker, Malabika; Jahn, Albrecht (© 2016 BMJ Global Health, 2018)
This article was published in the BMC Infectious Diseases [© 2017 BMC Infectious Diseases] and the definite version is available at : https://doi.org/10.1136/bmjgh-2016-000217 . The Journal's website is at: http://gh.bmj.com/content/2/1/e000217